Application of Ott’s mine coordinate system in the past and in present day - Staňková, Hana; Černota, Pavel (Geodesy and Cartography, 2013)
The coal district system of coordinates for mines located in the Ostrava region was established in 1858 by Dipl. Ing. František Ott, Surveyor of the Emperor Ferdinand Northern Railway (Severní dráha Ferdinandova). Coordinates of all significant points of existing mine shafts, characteristic mine surface points, and points in terrain, were determined by establishing mine triangulation within the Western part of the Ostrava-Karviná Coal District (OKR) on an area comprising almost 58 km2. Said points were stabilized by granite stones. The reason to establish this system of coordinates was to determine the points of a uniform basis of coordinates for making surveys both on the mine surface, i.e. for connecting the underground mine working, and simultaneously for removing any discrepancies occurring with respect to mine boundaries among particular proprietors, i.e. to allow for exact demarcation of mine areas bestowed to them by the state. Thus, nowadays Ott’s system of coordinates that used to be applied during the period, in which within the OKR redevelopment works took place, like abatement the coal mining consequences.